AI-Powered Customer Engagement In Women-Led Businesses (International Journal of Environmental Sciences, 2025)
Businesses are undergoing a transformation because of the implementation of artificial intelligence (AI), which is improving customer engagement, operational efficiency, and individualized marketing tactics. This study piece investigates the influence that artificial intelligence has on increasing consumer engagement in businesses that are run by women. The utilization of artificial intelligence provides female entrepreneurs with several options, including the enhancement of consumer relations through digitization, AI in social media, and personalization. Number of challenges are presented by the adoption of artificial intelligence, including the technical complexities of AI technology, concerns over data privacy, and biases that are inherent in algorithms. This article reviews the current literature, analyses the advantages and obstacles encountered by women entrepreneurs in integrating artificial intelligence technology, and offers guidance on the practical application of AI to enhance consumer engagement and sustain business growth.